2015
DOI: 10.1111/papr.12357
|View full text |Cite
|
Sign up to set email alerts
|

Cost Burden of Chronic Pain Patients in a Large Integrated Delivery System in the United States

Abstract: Chronic pain conditions impose a substantial burden on the healthcare system, with musculoskeletal conditions associated with the highest overall costs. Costs appeared to be primarily related to use of outpatient services. This type of research supports integrated delivery systems as a source for assessing opportunities to improve patient outcomes and lower the costs for chronic pain patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 29 publications
0
39
0
1
Order By: Relevance
“…The majority of studies were from USA ( n = 28) , followed by UK ( n = 4 studies) , Spain ( n = 3 studies) and Canada ( n = 3 studies) , with single studies from Norway , Denmark , Australia and India . There were no studies that compared data from multiple countries.…”
Section: Resultsmentioning
confidence: 99%
“…The majority of studies were from USA ( n = 28) , followed by UK ( n = 4 studies) , Spain ( n = 3 studies) and Canada ( n = 3 studies) , with single studies from Norway , Denmark , Australia and India . There were no studies that compared data from multiple countries.…”
Section: Resultsmentioning
confidence: 99%
“…3,24,25 When these comorbidities exist, healthcare costs are considerable higher. 27,28 Besides psychosocial factors regarding dealing with pain (such as fear of movement, pain catastrophizing, low pain self-efficacy, and passive pain coping), depression, anxiety and somatization, influence the prognosis of people with musculoskeletal pain. 3,18,36 Positively influencing these psychosocial factors optimizes recovery.…”
Section: Introductionmentioning
confidence: 99%
“…An interesting study from the Henry Ford Health System looked at the cost burden of patients with chronic pain by creating a de-identified, integrated administrative database in which both clinical information from the electronic medical record (EMR) and resource utilization data was searchable (16). This study reported on the rates of outpatient visits, imaging, opioid prescriptions, and associated costs, including global costs.…”
Section: Discussionmentioning
confidence: 99%